Classical and Molecular Identification of Thermotolerant Campylobacters from Poultry Meat - Tina Zorman; Sonja Smole Možina (Food Technology and Biotechnology, 2002)
Poultry meat samples from Slovenian retail market were examined for the presence of thermotolerant campylobacters. The isolates were identified by phenotypic and genotypic methods. ISO 10272 recommendations were followed for phenotypic identification. Different PCR assays, targeting species specific DNA regions in C. jejuni and C. coli, were checked for their applicability in identification. High degree of tested samples was positive (27/33), with significant proportion of C. coli (32 %) among identified strains. High percentage of C. jejuni strains (54 %) were hippurate negative. Phenotypic identification was therefore found to be inconvenient because of the presence of the strains with atypical phenotype and possible misinterpretation of test results. Multiplex PCR, targeting hippuricase gene in C. jejuni and species specific region in C. coli, was found to be an efficient method that allowed fast, simple and accurate identification of C. jejuni and C. coli. FlaA PCR is a reliable method to identify the group C. jejuni/C. coli, but it does not differentiate between the two species. CdtB PCR is inconvenient because of many false negative and some false positive results.